The relationship between DNA modifications and mutations in cancer - Tomkova, M (2017)
Somatic mutations are the main triggers that initiate the formation of cancer. Large sequencing data sets in recent years revealed a substantial number of mutational processes, many of which are poorly understood or of completely unknown aetiology. These mutational processes leave characteristic sequence patterns, often called "signatures", in the DNA. Characterisation of the mutational patterns observed in cancer patients with respect to different genomic features and processes can help to unravel the aetiology and mechanisms of mutagenesis. Here, we explored the effects of DNA modifications and DNA replication on mutagenesis. The most common mutation type, C>T mutations in a CpG context, is thought to result from spontaneous deamination of 5-methylcytosine (5mC), the major DNA modification. Much less is known about the mutational properties of the second most frequent modification, 5-hydroxymethylcytosine (5hmC). Integrating multiple genomic data sets, we demonstrate a twofold lower mutagenicity of 5hmC compared to 5mC, present across multiple tissues. Subsequently, we show how DNA modifications may modulate various mutational processes. In addition to spontaneous deamination of 5mC, our analysis suggests a key role of replication in CpG>TpG mutagenesis in patients deficient in post-replicative proofreading or repair, and possibly also in other cancer patients. Together with an analysis of mutation patterns observed in cancers exposed to UV light, tobacco smoke, or editing by APOBEC enzymes, the results show that the role of DNA modifications goes beyond the well-known spontaneous deamination of 5mC. Finally, we explored which of the known mutational processes might be modulated by DNA replication. We developed a novel method to quantify the magnitude of strand asymmetry of different mutational signatures in individual patients followed by evaluation of these exposures in early and late replicating regions. More than 75 % of mutational signatures exhibited a significant replication strand asymmetry or correlation with replication timing. The analysis gives new insights into mechanisms of mutagenicity in multiple signatures, particularly the so far enigmatic signature 17, where we suggest an involvement of oxidative damage in its aetiology. In conclusion, our results suggest that DNA replication or replication-associated DNA repair interacts with most mutagenic processes.